2014
DOI: 10.4103/0019-5413.139829
|View full text |Cite
|
Sign up to set email alerts
|

Understanding risks and complications in the management of ankle fractures

Abstract: Ankle fracture (AF) is a common injury with potentially significant morbidity associated with it. The most common age groups affected are young active patients, sustaining high energy trauma and elderly patients with comorbidities. Both these groups pose unique challenges for appropriate management of these injuries. Young patients are at risk of developing posttraumatic osteoarthritis, with a significant impact on quality of life due to pain and impaired function. Elderly patients, especially with poorly cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 61 publications
1
23
0
2
Order By: Relevance
“…Postoperative infection, wound dehiscence, failed bone healing, hardware failure, loss of reduction/fixation, pulmonary embolism, below-knee amputation, and mortality, are all reported complications following ankle ORIF. 29 Despite open reduction and internal fixation of ankle fractures, visualization of the entire joint is difficult and thus treatment of associated intraarticular injuries may be difficult to preform. Soohoo et al retrospectively reviewed a database of 57 183 patients who had undergone ORIF of a lateral malleolar, bimalleolar, or trimalleolar ankle fracture and found that the overall rate of short-term complications was low, including the rates of pulmonary embolism (0.34%), mortality (1.07%), wound infection (1.44%), amputation (0.16%), and need for revision ORIF (0.82%).…”
Section: Traditional Ankle Fracture Orifmentioning
confidence: 99%
“…Postoperative infection, wound dehiscence, failed bone healing, hardware failure, loss of reduction/fixation, pulmonary embolism, below-knee amputation, and mortality, are all reported complications following ankle ORIF. 29 Despite open reduction and internal fixation of ankle fractures, visualization of the entire joint is difficult and thus treatment of associated intraarticular injuries may be difficult to preform. Soohoo et al retrospectively reviewed a database of 57 183 patients who had undergone ORIF of a lateral malleolar, bimalleolar, or trimalleolar ankle fracture and found that the overall rate of short-term complications was low, including the rates of pulmonary embolism (0.34%), mortality (1.07%), wound infection (1.44%), amputation (0.16%), and need for revision ORIF (0.82%).…”
Section: Traditional Ankle Fracture Orifmentioning
confidence: 99%
“…Inadequate immobilization may result in further damage, putting the patient at greater risk for the development of post-traumatic osteoarthritis, which accounts for 70% of all cases of ankle osteoarthritis. 10 POCUS can play a critical role in identifying and correctly characterizing ankle fractures. POCUS is an important imaging modality in fracture assessment due to its availability at the patient’s bedside, ease of use, and multiplanar diagnostic capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of ankle joint arthritis is posttraumatic with estimated incidence to be in the region of 70%; rotational injuries being the commonest cause. The risk of venous thromboembolism (VTE) is reported to be low in patients with ankle fracture; deep vein thrombosis (DVT) (0.12%) and pulmonary embolism (PE) (0.17%) [ 55 ].…”
Section: Complicationmentioning
confidence: 99%
“…In the most severe cases, this can lead to amputation and mortality. Therefore, individualized approach to the management of AF is vital [ 55 ]. Elderly and diabetic patients are at particular risk of complications.…”
Section: Prognosismentioning
confidence: 99%